Rurality and warfare: Portugal in the context of the peninsular war (1807/1811) - Couceiro, Pedro (2014)
This paper aims to analyze the impact of the state of war experienced by rural populations during the Napoleonic wars that Portugal suffered between 1807-1811, a period known as the Peninsular War. The repercussions of this sequence of armed events could not have been more traumatic. In fact, the French invasions of Portugal appear as a violent hurricane that devastated the whole country and, directly or indirectly, have shaken the structures of the Ancient Regime. Firstly, because they voted the kingdom to a governance problem, re legating to the local power the mission of organizing the defense and protection of populations; secondly, because it meant a huge economic constraint. The depopulation of rural communities caused the rupture of economic and commercial relations between cities and the countryside, and at the same time, it increased the number of the discontent among various sectors of society. These adverse effects extended themselves to the whole territory, and contrary to what might be expected, the isolation of rural communities did not serve as protection. It rather caused a greater exposure of the rural heritage and therefore greater vulnerability of their populations affected by the passage and fixation of the armies